Environmental Flows : Saving Rivers in the Third Millennium. - Arthington, Angela H. (Freshwater ecology series., 2012)
Environmental Flows describes the timing, quality, and quantity of water flows required to sustain freshwater and estuarine ecosystems and the human well-being and livelihoods that depend upon them. It answers crucial questions about the flow of water within and between different kinds of ecosystems. What happens when the flow or the availability of water is curtailed or diverted, either naturally or by human activity? How will climate change alter the availability of water and impact aquatic ecosystems? Methodological developments from the simplest hydrological formulas to large-scale framew.